2018
DOI: 10.1002/jhbp.540
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for failure of early recovery from pancreatoduodenectomy despite the use of enhanced recovery after surgery protocols and a physical aging score to predict postoperative risks

Abstract: Advanced age, poor nutrition, and serious illnesses can cause ERAS protocol failure. The PA score is effective for predicting postoperative progress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
16

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 40 publications
1
9
0
16
Order By: Relevance
“…We determined that patients in the late-discharge group were significantly older and had a higher rate of CDC grade ≥ IIIa than those in the early-discharge group. Previous studies have shown that age and postoperative complications were associated with longer LOS (Xie et al 2013;Chaudhary et al 2015;Kim et al 2017;Kobayashi et al 2018;Pedziwiatr et al 2018;Jiang et al 2019). Our results were also consistent with those of the previous reports.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We determined that patients in the late-discharge group were significantly older and had a higher rate of CDC grade ≥ IIIa than those in the early-discharge group. Previous studies have shown that age and postoperative complications were associated with longer LOS (Xie et al 2013;Chaudhary et al 2015;Kim et al 2017;Kobayashi et al 2018;Pedziwiatr et al 2018;Jiang et al 2019). Our results were also consistent with those of the previous reports.…”
Section: Discussionsupporting
confidence: 93%
“…Our results were also consistent with those of the previous reports. The prolonged postoperative recovery probably reflects the decreased physical fitness and physiological capacity in older patients, as represented by frailty, in comparison with younger patients (Xie et al 2013;Kobayashi et al 2018). Therefore, it is anticipated that a higher rate of complications will occur in the late-discharge group than in the early-discharge group.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors, such as age, nutritional status, and serious comorbidity, can influence patients’ postoperative complication rates and the process of postoperative recovery[ 41 , 42 ]. The patients’ demographic data in the included studies was basically identical, so these influences may be eliminated for the outcomes in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest the e ciency of ERAS programmes for decreasing postoperative complications and morbidity, which is consistent with a previous RCT on ERAS protocols for OPD 12 . Moreover, a recent retrospective study found that lower pre-albumin level, higher ASA score and longer operative time were independent risk factors for failure of early recovery from OPD and increased complications of ERAS for OPD 10 . Of note, we found that more patients had pulmonary infections in the non-ER group compared with the ER group.…”
Section: Discussionmentioning
confidence: 99%
“…With the increased publication of ERAS guidelines to optimize patient outcomes after more complex and high-risk surgical procedures, there is growing enthusiasm and interest among healthcare professionals for studies on ERAS programmes in patients after open pancreatoduodenectomy (OPD) [8][9][10][11] . Encouragingly, most initial studies have shown the feasibility and safety of ERAS for OPD, such as early discharge 11 , decreased morbidity 12 , and fewer postoperative complications 13 .…”
Section: Introductionmentioning
confidence: 99%